DETERMINATION OF THE OXIDATIVE STABILITY OF BIODIESEL AND OILS BY ATR-FTIR SPECTROSCOPY AND MULTIVARIATE CALIBRATION (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
This work reports the use ATR-FTIR Spectroscopy and multivariate calibration as a method for determination of oxidative stability of biodiesel and oils. The prediction of the oxidative stability showed a good agreement with the results obtained by the EN14112 reference method Rancimat. The models presented high correlation between spectral data and induction periods. The R2 values of (0.9927 and 0.9921) indicated the accuracy of the models to predict the oxidative stability of vegetable oils and samples of biodiesel, respectively. Student’s t test showed no significant difference at 95% confidence between the actual and the predicted values of the periods of induction when applied for samples of vegetable oils and biodiesel.